Der Einfluß des Wechselkurses auf die deutsche Handelsbilanz - Jörg Clostermann (Deutsche Bundesbank, 1996)
The subject of the study is the impact of the exchange rate on Gennany's balance of trade. The analysis hence focuses on the significance of invoicing practices as weIl as the factors which determine export and import prices and the volumes.The results reveal a largely classical reaction on the part of Germany's balance of trade. In the long tenn, importers and, to a very large extent, exporters, too, pursue a policy of exchange rate pass-through. In this, importers pass on fluctuations in the exchange rate fuIly in their selling prices, which results in exchange-rate-induced changes in import prices. On the export side, this "rolling-over" strategy leads to Gennan products becoming dearer for foreign customers in the event of an appreciation of the Deutsche Mark. The export price hence remains largely unchanged when invoiced in domestic currency. In contrast to importers, however, exporters are prepared, even in the longer tenn, to neutralise a small part of the exchange rate fluctuations by varying their margins. Over the shorter tenn, this pricing to market may be observed quite clearly both on the import and on the export side. The conclusion implied by these results is that, in line with the classical view, prices are mainly cost-determined in the long run and hence that the law of one price may claim to a certain validity. By contrast, a more or less marked international differentiation in prices for the same goods may be observed over the shorter tenn ...
Keywords: 330; Leistungsbilanz; J-Kurve; Wechselkurs; Deutschland